The Impact Of Corporate Mudharabah Deposits On The Net Profits Of Islamic Banking Companies Listed On The Indonesia Stock Exchange - akbar Akbar; Lili Marlina; nurhaedah Nurhaedah (Economy Deposit Journal (E-DJ), 2022)
The purpose of this research is to determine the impact of Corporate Mudharabah Deposits on the Net Profits of Islamic Banking Companies Listed on the Indonesia Stock Exchange from 2011 to 2020. The population of this study includes Islamic commercial banks registered on the Indonesian stock exchange, with the number of samples determined by the purposive sampling approach, namely three companies: PT. BNI Syariah, PT. BRI Syariah, and PT. Sharia Mandiri. This is a quantitative study that uses published secondary data to examine the number of Mudharabah deposit savings and profits of Islamic banking institutions from 2011 to 2020 using the panel data approach. This study's test is a linear regression of panel data using the Stata 16 measuring instrument. The Common Effect model was chosen for this study based on the model's accuracy tests, which include the Chow test, Hausman test, and Lagrange Multiplier test. According to the study's findings, the amount of the Company's Mudharabah Deposits influences the level of net income earned by the company.